ANALISIS FAKTOR-FAKTOR TERHADAP UNDERPRICING SAHAM PERDANA - INDRA ARIFIN DJASHAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
This research aims to determine the effect of firm age, firm size, return on equity, debt to equity ratio, price earnings ratio, auditor reputation and underwriter reputation on the level of underpricing. And to determine which variables are the most dominant effect on the IPO. Underpricing as measured by the initial return is the dependent variable in this research. This research was conducted with the support of the data Indonesia Stock Exchange (IDX), which is the company doing an IPO in 2009 until 2012. Sampling was conducted using a non-probability sample selection method (purposive sampling) resulted in 68 companies as the study sample. Multiple regression model was used to test the relationship between the dependent and independent variables. The results of multiple regression analysis showed that the variables auditor reputation and underwriter reputation on underpricing significantly affect the direction of the negative coefficients for both variables. While variable firm age, firm size, return on equity, debt to equity ratio, price earnings ratio proved to have no significant effect on the occurrence of underpricing.